Amino-truncated NOV expression and its correlation with clinicopathologic features, prognosis, metastasis, and chemoresistance in bladder cancer - Dan Xiong; Yafei Xu; Hongbo Wang; Yunlin Ye (Cancer Biology & Therapy)
Nephroblastoma, an overexpressed gene (NOV) protein, plays an important role in proliferation, differentiation, angiogenesis, adhesion, invasion and tumorigenesis, but the function of amino-truncated NOV is different. This study is to investigate the role of amino-truncated NOV in the progression of bladder cancer. Using immunohistochemistry and Western blot analysis, we detected the amino-truncated NOV in bladder cancer, and statistical analysis was performed to estimate the association between the expression of amino-truncated NOV and the patient’s prognosis by SPSS 19.0. With transduction of amino-truncated NOV, we evaluated alteration for proliferation, migration, invasion and chemoresistance in bladder cancer cells, as well as some proteins related to Wnt/β-catenin pathway and epithelial–mesenchymal transition. The truncated variant of the NOV protein was located in a nucleus other than the cytoplasm and highly expressed in bladder cancer, which was also linked to higher pathological grade and positive lymph node metastasis as well as recurrence. The exact sequence of this truncated protein was confirmed, and it was a 26-kDa splicing. The truncated NOV protein found in bladder cancer was cut at the 187th amino acid of the full-length protein. It was also involved in bladder cancer progression and chemoresistance through a mechanism involving epithelial–mesenchymal transition (EMT) and the Wnt/β-catenin signaling pathway. Our findings provide experimental evidence that the nuclear NOV protein expression is a potential biomarker in the prognostic evaluation of bladder cancer and enhanced amino-truncated NOV expression is potentially important for bladder cancer cell invasion, metastasis and chemoresistance during progression.